Eksplorasi Pengalaman Housekeeping dalam Penggunaan Checklist dan Sistem Pelaporan Elektronik di Renaissance Okinawa Resort - Raihanafa, Indira; Yuliamir, Henry (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to explore the housekeeping experience in using checklists and electronic reporting systems at Renaissance Okinawa Resort. The issue is focused on how these two instruments support work efficiency, data accuracy, and service quality in the housekeeping department. To approach this problem, the study applies operational management and hospitality technology theories. Data were collected through in-depth interviews with housekeeping staff, supervisors, and managers, as well as direct observations of daily activities, and were analyzed qualitatively using a thematic approach. The findings indicate that conventional checklists still serve an essential function as procedural control tools, while electronic reporting systems provide advantages in terms of speed, transparency, and real-time monitoring. The integration of both instruments was proven to enhance staff professionalism, strengthen interdepartmental coordination, minimize recording errors, and accelerate guest complaint handling. This study concludes that the combination of manual checklists and digital systems represents an effective strategy for achieving modern, accountable, and service-oriented housekeeping performance in the hospitality industry.